Long-term Outcome After Multiple Burr Hole Surgery in Children With Moyamoya Angiopathy: A Single-Center Experience in 108 Hemispheres. Issue 6 (20th February 2017) - Blauwblomme, Thomas; Mathon, Bertrand; Naggara, Olivier; Kossorotoff, Manoelle; Bourgeois, Marie; Puget, Stéphanie; Meyer, Philippe; Brousse, Valentine; de Montalembert, Marianne; Brunelle, Francis; Zerah, Michel; Sainte-Rose, Christian
Abstract: BACKGROUND: Multiple burr hole (MBH) surgery is a simple, safe, and effective indirect technique of revascularization in moyamoya angiopathy (MM). However, it is not yet recognized as a first-line treatment. OBJECTIVE: To assess the long-term outcome and perioperative complications in a large single-center cohort of children with MM who underwent burr hole surgery. METHODS: This study is a retrospective analysis of children who underwent surgery for MM in a national reference center for pediatric stroke between 1999 and 2015. Sixty-four children (108 hemispheres, median age 7 years) were consecutively treated. The indication for revascularization was previous stroke or transient ischemic attack (TIA) or rapidly progressive disease on brain magnetic resonance imaging (MRI) and digital subtraction angiography. Children were followed with clinical examinations, telephone interviews, and MRI with any clinical recurrence of stroke or TIA used as the primary endpoint. Surgical mortality and morbidity were documented. RESULTS: Sixty-four patients were operated (bilateral MBH n = 39, unilateral procedure n = 25). At a mean follow-up of 4.2 years and 270.6 patient years, 89.1% of patients had not suffered any recurrent stroke or TIA. A second surgery was required in 5 cases after unilateral revascularization, and in 3 cases after bilateral MBH. Mortality associated with the procedure was 0. Postoperative Matsushima angiographic grading was the only predictive factor of ischemic recurrence ( P = .036). CONCLUSION: In pediatric MM, MBH compares favorably to other indirect or direct revascularization techniques in children in the prevention of stroke or TIA.